2022
DOI: 10.53930/27892182.dialogos.7.8
|View full text |Cite
|
Sign up to set email alerts
|

A brief qualitative study of indigenous traditional medicine providers in Timor-Leste

Abstract: Providers of Traditional Timorese Medicine are an essential resource in rural communities, contributing greatly to the overall health of individuals in Timor-Leste. Their identity and role in healthcare has not been widely investigated and functions outside of the National Health System. The objective of this qualitative study is to describe the role of providers of Timorese Traditional Medicine in Timor-Leste and their practice of medicine. To perform this research, semi-structured interviews were performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Previous researchers documented similar findings, that spiritual calling into healing is an intergenerational familial natural gift [ 16 , 23 , 63 ]. Another researcher found that anointment into healing using ancestral spirits is involuntary, and may manifest through challenges of illness [ 64 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Previous researchers documented similar findings, that spiritual calling into healing is an intergenerational familial natural gift [ 16 , 23 , 63 ]. Another researcher found that anointment into healing using ancestral spirits is involuntary, and may manifest through challenges of illness [ 64 ].…”
Section: Discussionsupporting
confidence: 61%
“…This is supported by recommendations that trained and categorised healers with recognised competencies should be identified, profiled, registered, monitored and evaluated and get certified by accredited institution that understand, contextualize, appreciate, and recognise them and their practices [ 14 , 15 ]. More authors argue that this would assist to harmonise, streamline, regulate and promote informal skills development, qualifications, and accreditation of their practices, therapies, and services [ 16 19 ]. Nonetheless, the practices of traditional healers do not lend themselves to evaluation, measurement, and precise data, using qualitative and quantitative methods [ 20 ], even though local and indigenous ways of knowing have long co-existed with mainstream sciences [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their description of illness is embedded in their culture. Just like other authors who assert that illness is associated with misfortunes (63) and somatic experiences reflective of bad relations with supernatural forces and ancestral spirits (64). Illness has various possible cause that may include, but not limited to curses, witchcraft, and failure to observe social taboos (65).…”
Section: Discussionmentioning
confidence: 89%
“…Some authors documented illness as an unclear and unnamed spiritual health condition caused by ancestral spirits and witchcraft (40), whose description of illness is embedded in people’s cultures. Other authors assert that illness is associated with misfortunes (59,60) and somatic experiences reflective of bad relations with supernatural forces and ancestral spirits (61). Illness has various possible cause that may include, but not limited to curses, witchcraft, and failure to observe social taboos (62), while others indicate that illness may manifest as a divine punishment (42,63).…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have for long established that in Africa, the relationships between the living and their ancestors are believed to be mutually beneficial (43,44), and linked by spirit mediums (45,46). Furthermore, illness and associated suffering are socialized (21) through ritual healing and symbolic interpretations (20) in line with cultural, spiritual and supernatural causal relations (40,(47)(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%